Quality of life and associated factors in Swiss trans people: a cross-sectional study - Garcia Nuñez, David; Frigerio, Giulia; Perler, Laura D.; Jäggi, Tiziana; Schönbucher, Verena; von Känel, Roland (Frontiers in Psychiatry, 2024)
Background: Experiences of stressful life events during transition may have a negative impact on quality of life (QoL) in trans persons. Little attention has been paid to this population in Switzerland, resulting in sparse data on their QoL and associated social factors.Methods: 30 participants were recruited during their medical transition treatment and surveyed on their experiences within this time period (13 months after the first medical intervention on average). After performing a diagnostic interview to evaluate their mental health, health-related QoL, psychological distress, self-esteem and the impact of life events that occurred in the last six months on participants were further assessed.Results: Approximately 17% of participants had suffered from major depression, 43% reported having had suicidal thoughts or having attempted suicide, and 43% suffered from an anxiety disorder. Psychological distress was twice as high compared to the norm values of the cis population. With regard to QoL, trans individuals showed impairments in the mental domain. Stressful life events were particularly evident on a psychological and social level.Analysis showed a negative correlation between impact of life events and mental QoL and between psychological distress and mental QoL. At the same time, there was a positive correlation between self-esteem and mental QoL. Psychological distress and self-esteem emerged as independent significant predictors of mental QoL.This study shows lowered mental QoL and associations of low mental QoL with psychological distress, low self-esteem and stressful life events in trans individuals in Switzerland. The findings concur with the Gender Minority Stress Model and point out that medical transition must not be viewed in isolation but must be embedded in the framework of integrative psychosocial support.